Study on Energy Savings Based on Lighting System Using Low-Cost Home Energy Management System (HEMS) - Nurnaili Afifah Mohd Rusli; Farahiyah Mustafa; Sim Sy Yi; Nor Aira Zambri (Progress in Engineering Application and Technology, 2022)
As the population and economic growth rapidly, demand on energy consumption also rising in many countries nearly every year for at least half a century based on the article of Energy Production and Consumption by Hannah Ritchie and Max Roser. The study focused on design and developed low-cost energy monitoring as to monitor the energy consumption on lighting system for HEMS and thus study on the energy savings evaluation. Based on the results, it shows that the energy metering for monitoring the HEMS came to triumph as it displays the output of the current, power, peak power and energy consumption that also leads to the successful of the study on energy savings of the HEMS as it shows that the low wattage loads with higher energy efficiency has the highest total annual energy savings for a long period of time. By practicing this study, the production of energy wasted and energy consumption reduced as the energy savings increasing for the HEMS.